(3GdaQjOI GdYdjG aj TQhW GdOYGAs - (3eLghds ((3YHO GdQMef Hf GdSjO CMeO GdNWjH GdOeTbjs)
(3ChdgG (B:s
(3GdMeO ddg MeOG jhGaj fYeg hjcGaF eRjOg hCTcQg TcQG jhGRj EfYGeg GdYOjOICeG HYO aEfj CMHHJ Cf CPcQ HYV ahGFO gPG GdcJGH edNUGaCbhd hHGddg GdJhajb hgh GdgGOj dCbhe WQjb bGd eG eYfGg GdaGVd ejQc TGgs
(3BNQgG (B:s
(3hGdUdGI hGdSdGe GdCJeGf GdCcedGf Ydi CTQa GdeNdhbGJ hYdi Bdg hYTQJg GdWGgQI hCUMGHg GdSGOI GdfLhe GdRGgQI eG UOMJ GdMeGFe Ydi GdCTLGQ hSLYJ aj CjcgG GdCWjGQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs